The History of Development of Philosophy in Time Ancient Greece - Fusvita Dewi; Salminawati Salminawati; Nur Ikhwan Harahap; Risma Br Purba (Edumaspul: Jurnal Pendidikan, 2023)
Philosophy does not escape a long history, of course, it takes a very long process to be studied and practiced. Thus, there will be many periods including ancient Greece where early humans used reason and tried to erase Greek mythology. The history of philosophy in ancient Greece was the beginning of human thought about the universe, then the Greek philosopher was born who expressed thoughts about the universe. Greek philosophy is also more prominent towards the West, as it is in Western Europe.